Rectal temperature correction overestimates the frequency of exercise-induced hypoxemia - Shipp, N. J.; Scroop, G. C.; Jackson, S. C.; Holmes, M. D.; Thornton, A. T.; Gore, C. J. (Medicine & Science in Sports & Exercise, 2004)
NTRODUCTION: Exercise-induced hypoxemia (EIH) occurs in an uncertain proportion of endurance trained athletes. Whereas blood gas measurements must be corrected for core temperature at the time of sampling, the commonly used rectal temperature readings may not be the most appropriate. METHODS: Ten males [mean peak oxygen uptake, (.-)VO(2peak), 65.4 +/- 7.0 mL x kg x min] performed incremental treadmill exercise from rest to exhaustion with radial artery blood samples collected at the end of each 2-min workload for gas analysis. The thermogenic effect of exercise was monitored with rectal, arterial blood, and esophageal temperature probes, and the values obtained at all three sites, simultaneous with blood sampling, were used to correct the standard blood gas measurements made at 37 +/- C. RESULTS: The mean increase in rectal temperature across exercise (1.4 +/- 0.4 +/- C) was approximately half that recorded in radial arterial blood (2.3 +/- 0.5+/- C) and the esophagus (2.4 +/- 0.5 degrees C). In consequence, the uncorrected fall in PaO2 across exercise of 15.4 +/- 8.2 mm Hg was reduced to 8.4 +/- 7.7 mm Hg when corrected for rectal temperature, and to 2.9 +/- 7.4 and 2.1 +/- 8.8 mm Hg when corrected for arterial blood and esophageal temperatures. Using a fall of > or = 10 mm Hg as the index of EIH, the proportion in the 10 subjects in the present study fell from 80% (uncorrected) through 50% (rectal correction) to 20% (arterial blood and esophageal corrections). CONCLUSION: When correcting arterial blood gas values for the thermogenic effects of exercise, the proportion of athletes meeting the definition of EIH depends on the site of core temperature measurement.